Positive grid and preparation method thereof, positive plate and preparation method thereof, and lead-acid storage battery

By using multiple alloys to prepare the positive plate grid of lead-acid battery, the problem of easy deformation and failure of the positive plate grid in the prior art is solved, the corrosion resistance and charging acceptance of the battery are improved, and the cycle life of the battery is significantly extended.

CN119812355APending Publication Date: 2025-04-11ANHUI LEOCH POWER SUPPLY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411979161.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The positive plate grid of existing lead-acid batteries is easily oxidized during charging, resulting in deformation and failure, resulting in shortening of battery life.

Method used

The positive electrode grid is prepared using multi-alloys, including Ca, Sn, Al, Ag, La and other elements, and is prepared by specific steps such as lead melting, slag-brushing, adding metal components, cooling, sampling and testing, casting and hardening.

Benefits of technology

It improves the corrosion resistance of the alloy, the hardness and elongation of the plate gate, improves the interface properties between the plate gate and the active substance, and improves the charging acceptance and cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005221121430000121
    Figure BDA0005221121430000121
  • Figure BDA0005221121430000131
    Figure BDA0005221121430000131
  • Figure HDA0005221121440000011
    Figure HDA0005221121440000011
Patent Text Reader

Abstract

The invention discloses a positive grid and a preparation method thereof, a positive plate and a preparation method thereof, and a lead-acid storage battery, and relates to the technical field of lead-acid storage batteries. The invention provides a positive plate grid. The positive plate grid is prepared from Ca, Sn, Al, Ag, La and Pb. The preparation method comprises the following steps: S1, melting lead; s2, slag removal; s3, adding metal components; s4, cooling; s5, sampling and testing; s6, casting is conducted; and S7, hardening. The invention further provides a positive plate which is obtained from the positive plate grid and positive lead plaster. The invention also provides a lead-acid storage battery which comprises the positive plate. The positive plate grid is made of the multi-component alloy, so that the corrosion resistance of the alloy and the hardness and elongation of the grid can be improved, the hydrogen evolution and oxygen evolution overpotential can be improved, meanwhile, the interface property of the grid and an active substance can be improved, and the charging acceptance of an electrode can be improved; according to the positive plate, a positive lead paste formula, a paste mixing process and a curing and drying process are improved, more tetrabasic lead sulfate is obtained, and the cycle life of a storage battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lead-acid batteries, and in particular to a positive electrode grid and a preparation method thereof, a positive electrode plate and a preparation method thereof, and a lead-acid battery. Background Art

[0002] With the continuous development of society, lead-acid batteries are being used in different scenarios. Especially in the field of grid energy storage, customers have higher requirements for the life performance of lead-acid battery products. Therefore, it is necessary to develop tubular batteries for ultra-long life cycles. Ultra-long life tubular batteries are mainly used in communications, electricity, solar / wind energy storage power supplies and other fields to fully meet market demand. The cycle life of ultra-long life tubular batteries is mainly affected by factors such as alloys, formulas, and processes. After dissecting and analyzing the failed battery after 3900 cycles of 40% DOD, it was found that the battery shell was severely swollen and deformed, and the positive terminal of the battery cover was cracked. The reason for the analysis is that the tubular positive plate grid is oxidized into lead sulfate and lead dioxide during the charging process. Due to the formation of the lead dioxide corrosion layer, the lead alloy generates stress, which causes the grid to grow and deform linearly. The growth force of the positive plate is applied to the pole terminal to break the battery cover, and finally leads to the loss of support and failure.

[0003] The cracking at the positive terminal of the battery cover accelerates the water loss of the battery, leading to thermal runaway, and the battery swells and deforms. Since the ultra-long-life tubular battery is a maintenance-free battery, the positive plate grid is made of lead-calcium alloy. Advantages of lead-calcium alloy: low resistance, its resistivity is close to that of pure lead. High hydrogen evolution overpotential, less water decomposition, and good maintenance-free performance. Calcium has a negative potential and will not dissolve and transfer from the positive plate to the negative electrode. However, lead-calcium alloy has poor creep resistance, the positive grid grows seriously, and the alloy is too soft, so the casting is easy to deform. In addition, calcium is oxidized during the casting process of the positive grid, resulting in serious calcium loss and difficult to control the content. Lead-calcium alloy batteries have poor deep cycle capabilities, and lead sulfate, calcium sulfate or semiconductor oxides are formed at the interface between the grid and the active material. This barrier layer greatly reduces the battery's charging capacity. The formula and curing process of the positive plate are also important factors affecting the battery life. The paste formula and curing process affect the formation of tribasic lead sulfate and tetrabasic lead sulfate in the positive plate, and further determine the ratio of α-PbO2 and β-PbO2 content after the plate is formed. The crystal size of β-PbO2 is about half of that of α-PbO2, so β-PbO2 crystals have a larger real surface area than α-PbO2, thus having a higher discharge capacity. However, due to the coarse α-PbO2 particles, the particles are tightly bound together and have a longer service life, while the soft and fine β-PbO2 particles are poorly bound together, so they are easy to fall off during the charge and discharge process. Summary of the invention

[0004] In order to solve at least one of the above technical problems, a positive grid capable of extending the service life of a lead-acid battery is developed. The present application provides a positive grid and a preparation method, a positive plate and a preparation method, and a lead-acid battery.

[0005] In one aspect, the present application provides a positive electrode grid, which is prepared from the following components:

[0006] Ca: 0.070wt%~0.150wt%;

[0007] Sn: 0.450wt%~1.250wt%;

[0008] Al: 0.005wt%~0.035wt%;

[0009] Ag: 0.002wt%~0.005wt%;

[0010] La: 0.01wt%~0.025wt%;

[0011] Pb: margin.

[0012] Optionally, the positive electrode grid of the present application is prepared from the following components:

[0013] Ca: 0.070wt%~0.150wt%;

[0014] Sn: 0.600wt%~0.900wt%;

[0015] Al: 0.015wt%~0.030wt%;

[0016] Ag: 0.003wt%~0.005wt%;

[0017] La: 0.012wt%~0.018wt%;

[0018] Pb: margin.

[0019] In a second aspect, the present application provides a method for preparing the above-mentioned positive electrode grid, comprising the following steps:

[0020] S1. Melting Lead

[0021] First add some lead and heat it to make it melt;

[0022] S2, slag removal

[0023] Heat up, add sodium nitrate and sodium hydroxide and stir for 10-15 minutes, the lead slag will be yellow particles, remove the slag; add lead slag reducer, stir for 5-10 minutes, then stop the machine and remove the slag;

[0024] S3. Adding metal components

[0025] Raise the temperature again, slowly add the formulated amount of aluminum, magnesium, lanthanum, calcium, and tin while stirring, and stir for 5 to 15 minutes;

[0026] S4. Cooling

[0027] Add the remaining lead in the formula, cool down, and stir for 5 to 15 minutes;

[0028] S5. Sampling and testing

[0029] After the sampling and testing are qualified, the liquid is released;

[0030] S6. Casting

[0031] preparing the grid by casting;

[0032] S7, Hardening

[0033] Hardening in a drying room.

[0034] Optionally, during the slagging step S2, the temperature is raised to 640±10°C;

[0035] and / or, S3, adding metal components, raising the temperature to 690±10°C;

[0036] And / or, S4, cooling down to 550±10°C.

[0037] Optionally, in the casting step S6, the casting temperature is 400°C to 480°C, and the casting plate pressure is 9 to 12 MPa.

[0038] Optionally, in S7, hardening, the temperature is 85° C. to 95° C., and the time is 4 h to 5 h.

[0039] In a third aspect, the present application provides a positive electrode plate, comprising the above-mentioned positive electrode grid and positive electrode lead paste, wherein the positive electrode lead paste comprises the following components:

[0040] Red lead: 15wt%~35wt%;

[0041] Sulfuric acid solution: 6wt%~8wt%;

[0042] Deionized water: 12wt%~18wt%;

[0043] Tetrabasic lead sulfate: 0.3wt% to 0.5wt%;

[0044] Graphite: 0.5wt%~1.0wt%;

[0045] Polytetrafluoroethylene emulsion: 0.12wt%~0.18wt%;

[0046] Antimony trioxide: 0.6wt%~1.0wt%;

[0047] Stannous sulfate: 0.6wt%~1.0wt%;

[0048] The rest is lead powder.

[0049] In a fourth aspect, the present application provides a method for preparing the above-mentioned positive electrode plate, comprising the following steps:

[0050] Step 1: Add lead powder into a paste mixer, then add red lead-antimony trioxide-stannous sulfate-graphite-tetrabasic lead sulfate in sequence, and mix and stir for 4-5 minutes;

[0051] Step 2: Add deionized water while stirring for 2 to 3 minutes, and continue to mix and stir for 5 to 6 minutes after adding the deionized water; during the mixing and stirring process, mix the polytetrafluoroethylene emulsion and deionized water in a volume ratio of 1:1 and add the mixed solution for 4 to 5 minutes;

[0052] Step 3: After the water mixing is completed, sulfuric acid solution is added in a stirring state, and the acid addition time is controlled within 8 to 12 minutes. The maximum temperature during the acid addition process does not exceed 65°C. After the acid is added, continue mixing and stirring for 10 to 12 minutes;

[0053] Step 4: Stop the machine to measure the density of the lead paste. The density of the lead paste should be between 3.4 and 3.5 g / cm 3 between;

[0054] Step 5: Apply the prepared lead paste on the positive electrode grid to obtain a positive electrode plate;

[0055] Step 6: The positive plate is sent to the curing and drying room for curing and drying within 40 minutes.

[0056] Optionally, the curing and drying described in step 6 includes the following stages:

[0057] The first stage is curing, with a curing temperature of 55°C, a humidity of 99RH, and a time of 12h;

[0058] The second stage is curing, with a curing temperature of 60°C, a humidity of 95RH, and a time of 12h;

[0059] The third stage is curing, with a curing temperature of 65°C, a humidity of 90RH, and a time of 6 hours;

[0060] The fourth stage is curing, with a curing temperature of 65°C, a humidity of 85RH, and a time of 6 hours;

[0061] The fifth stage is curing, with a curing temperature of 60°C, a humidity of 70RH, and a time of 6 hours;

[0062] The sixth stage is curing, with a curing temperature of 60°C, a humidity of 55RH, and a time of 6 hours;

[0063] The seventh stage is drying, with a drying temperature of 65°C, a humidity of 45RH, and a time of 8h;

[0064] The eighth stage is drying, with a drying temperature of 72°C, a humidity of 10RH, and a time of 12 to 16 hours.

[0065] In a fifth aspect, the present application provides a lead-acid battery comprising the above-mentioned positive electrode plate.

[0066] In summary, the present invention includes at least one of the following beneficial technical effects:

[0067] 1. The use of multi-element alloys can improve the corrosion resistance of the alloy, the hardness and elongation of the grid, increase the overpotential of hydrogen and oxygen evolution, and at the same time improve the interface properties between the grid and the active material, and improve the charge acceptance capacity of the electrode;

[0068] 2. The positive lead paste formula and paste process of the present application can obtain more tetrabasic lead sulfate, which is more beneficial to the cycle life of the battery;

[0069] 3. The curing and drying process of the present application is adopted. During the curing and drying process, the needle-shaped and rod-shaped crystal structures of 3PbO·PbSO4·H2O and the columnar crystal structure of 4PbO·PbSO4·H2O are cross-linked to form a solid fiber network structure, which plays a good role in enhancing the bonding force between particles in the lead paste and the strength of the plate;

[0070] 4. The addition of additives such as polytetrafluoroethylene and graphite improves the binding force of lead paste and the utilization rate of active materials, so that the battery has better charge and discharge performance. At the same time, it can improve the structure of grid corrosion products and maintain the long-term stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0071] Figure 1 This is a SEM image of the positive electrode lead paste in the prior art;

[0072] Figure 2 is a SEM image of the positive electrode lead paste prepared in Example 1;

[0073] Figure 3 Performance test diagram of battery application example 1. DETAILED DESCRIPTION

[0074] The present application is further described in detail below with reference to the accompanying drawings and embodiments.

[0075] In the following examples of the present application, the main components involved, unless otherwise specified, were purchased from commercially available products. Specific embodiments

[0077] Preparation Example 1

[0078] This preparation example is used to prepare a positive electrode grid, which is prepared from the following components: Ca: 0.070wt%; Sn: 0.450wt%; Al: 0.035wt%; Ag: 0.002wt%; La: 0.010wt%; Pb: balance; the specific steps are as follows.

[0079] First, add 90% of the formula amount of lead, heat and heat to melt the lead; heat to 640±10℃, add sodium nitrate and sodium hydroxide and stir for 10 minutes, the lead slag is yellow particles, and the slag is removed; add lead slag reducer, stir for 8 minutes, then stop the machine and remove the slag; raise the temperature to 690±10℃ again, slowly add the formula amount of aluminum, magnesium, lanthanum, calcium and tin under stirring, and stir for 10 minutes; add the remaining lead in the formula, cool to 550±10℃, and stir for 10 minutes; after sampling and testing, drain the liquid; prepare the grid by casting, the casting temperature is 420℃, and the casting pressure is 10MPa; perform hardening treatment in a drying room at a temperature of 90℃ and a time of 5h.

[0080] Preparation Example 2

[0081] This preparation example is used to prepare a positive electrode grid, which is prepared from the following components: Ca: 0.100wt%; Sn: 0.600wt%; Al: 0.030wt%; Ag: 0.003wt%; La: 0.012wt%; Pb: balance; the specific steps are as follows.

[0082] First, add 90% of the formula amount of lead, heat and heat to melt the lead; heat to 640±10℃, add sodium nitrate and sodium hydroxide and stir for 10 minutes, the lead slag is yellow particles, and the slag is removed; add lead slag reducer, stir for 8 minutes, then stop the machine and remove the slag; raise the temperature to 690±10℃ again, slowly add the formula amount of aluminum, magnesium, lanthanum, calcium and tin under stirring, and stir for 10 minutes; add the remaining lead in the formula, cool to 550±10℃, and stir for 10 minutes; after sampling and testing, drain the liquid; prepare the grid by casting, the casting temperature is 420℃, and the casting pressure is 10MPa; perform hardening treatment in a drying room at a temperature of 90℃ and a time of 5h.

[0083] Preparation Example 3

[0084] This preparation example is used to prepare a positive electrode grid, which is prepared from the following components: Ca: 0.015wt%; Sn: 0.750wt%; Al: 0.025wt%; Ag: 0.005wt%; La: 0.015wt%; Pb: balance; the specific steps are as follows.

[0085] First, add 90% of the formula amount of lead, heat and heat to melt the lead; heat to 640±10℃, add sodium nitrate and sodium hydroxide and stir for 10 minutes, the lead slag is yellow particles, and the slag is removed; add lead slag reducer, stir for 8 minutes, then stop the machine and remove the slag; raise the temperature to 690±10℃ again, slowly add the formula amount of aluminum, magnesium, lanthanum, calcium and tin under stirring, and stir for 10 minutes; add the remaining lead in the formula, cool to 550±10℃, and stir for 10 minutes; after sampling and testing, drain the liquid; prepare the grid by casting, the casting temperature is 420℃, and the casting pressure is 10MPa; perform hardening treatment in a drying room at a temperature of 90℃ and a time of 5h.

[0086] Preparation Example 4

[0087] This preparation example is used to prepare a positive electrode grid, which is prepared from the following components: Ca: 0.070wt%; Sn: 0.900wt%; Al: 0.015wt%; Ag: 0.005wt%; La: 0.018wt%; Pb: balance; the specific steps are as follows.

[0088] First, add 90% of the formula amount of lead, heat and heat to melt the lead; heat to 640±10℃, add sodium nitrate and sodium hydroxide and stir for 10 minutes, the lead slag is yellow particles, and the slag is removed; add lead slag reducer, stir for 8 minutes, then stop the machine and remove the slag; raise the temperature to 690±10℃ again, slowly add the formula amount of aluminum, magnesium, lanthanum, calcium and tin under stirring, and stir for 10 minutes; add the remaining lead in the formula, cool to 550±10℃, and stir for 10 minutes; after sampling and testing, drain the liquid; prepare the grid by casting, the casting temperature is 420℃, and the casting pressure is 10MPa; perform hardening treatment in a drying room at a temperature of 90℃ and a time of 5h.

[0089] Preparation Example 5

[0090] This preparation example is used to prepare a positive electrode grid, which is prepared from the following components: Ca: 0.100wt%; Sn: 1.150wt%; Al: 0.01wt%; Ag: 0.003wt%; La: 0.020wt%; Pb: balance; the specific steps are as follows.

[0091] First, add 90% of the formula amount of lead, heat and heat to melt the lead; heat to 640±10℃, add sodium nitrate and sodium hydroxide and stir for 10 minutes, the lead slag is yellow particles, and the slag is removed; add lead slag reducer, stir for 8 minutes, then stop the machine and remove the slag; raise the temperature to 690±10℃ again, slowly add the formula amount of aluminum, magnesium, lanthanum, calcium and tin under stirring, and stir for 10 minutes; add the remaining lead in the formula, cool to 550±10℃, and stir for 10 minutes; after sampling and testing, drain the liquid; prepare the grid by casting, the casting temperature is 420℃, and the casting pressure is 10MPa; perform hardening treatment in a drying room at a temperature of 90℃ and a time of 5h.

[0092] Preparation Example 6

[0093] This preparation example is used to prepare a positive electrode grid, which is prepared from the following components: Ca: 0.150wt%; Sn: 1.250wt%; Al: 0.005wt%; Ag: 0.002wt%; La: 0.025wt%; Pb: balance; the specific steps are as follows.

[0094] First, add 90% of the formula amount of lead, heat and heat to melt the lead; heat to 640±10℃, add sodium nitrate and sodium hydroxide and stir for 10 minutes, the lead slag is yellow particles, and the slag is removed; add lead slag reducer, stir for 8 minutes, then stop the machine and remove the slag; raise the temperature to 690±10℃ again, slowly add the formula amount of aluminum, magnesium, lanthanum, calcium and tin under stirring, and stir for 10 minutes; add the remaining lead in the formula, cool to 550±10℃, and stir for 10 minutes; after sampling and testing, drain the liquid; prepare the grid by casting, the casting temperature is 420℃, and the casting pressure is 10MPa; perform hardening treatment in a drying room at a temperature of 90℃ and a time of 5h.

[0095] In the following embodiments, the positive electrode lead paste involved adopts the following formula as an example: red lead: 20wt%; sulfuric acid solution: 6wt%; deionized water: 15wt%; tetrabasic lead sulfate: 0.3wt%; graphite: 0.5wt%; polytetrafluoroethylene emulsion: 0.15wt%; antimony trioxide: 0.8wt%; stannous sulfate: 0.8wt%; the rest is lead powder.

[0096] Example 1

[0097] This embodiment is used to prepare a positive electrode plate, including the positive electrode grid and positive electrode lead paste prepared in the above-mentioned Preparation Example 1. The specific preparation method is as follows.

[0098] Step 1: Add lead powder into a paste mixer, and then add red lead-antimony trioxide-stannous sulfate-graphite-tetrabasic lead sulfate in sequence, and mix and stir for 5 minutes.

[0099] Step 2: Add deionized water while stirring for 2 minutes. Continue to mix and stir for 5 minutes after adding the deionized water. During the mixing and stirring process, mix the polytetrafluoroethylene emulsion and deionized water in a volume ratio of 1:1 and add the mixed solution for 5 minutes.

[0100] Step 3: After the water mixing is completed, add sulfuric acid solution while maintaining stirring. The acid addition time is controlled within 10 minutes. The maximum temperature during the acid addition process does not exceed 65°C. After the acid is added, continue mixing and stirring for 10 minutes.

[0101] Step 4: Stop the machine to measure the density of the lead paste. The density of the lead paste should be between 3.4 and 3.5 g / cm 3 between.

[0102] Step 5: Apply the prepared lead paste on the positive electrode grid to obtain the positive electrode plate.

[0103] Step 6: The positive plate is sent to the curing and drying room for curing and drying within 40 minutes.

[0104] Curing and drying includes the following stages:

[0105] The first stage is curing, the curing temperature is 55℃, the humidity is 99RH, and the time is 12h.

[0106] The second stage is curing, with a curing temperature of 60°C, a humidity of 95RH, and a time of 12 hours.

[0107] The third stage is curing, with a curing temperature of 65°C, a humidity of 90RH, and a time of 6 hours.

[0108] The fourth stage is curing, with a curing temperature of 65°C, a humidity of 85RH, and a time of 6 hours.

[0109] The fifth stage is curing, with a curing temperature of 60°C, a humidity of 70RH, and a time of 6 hours.

[0110] The sixth stage is curing, with a curing temperature of 60°C, a humidity of 55RH, and a time of 6 hours.

[0111] Take samples for testing of free lead and water content: free lead content of the plate Pb≤4.0%, water content of the plate H2O≤5.0%.

[0112] The seventh stage is drying, with a drying temperature of 65°C, a humidity of 45RH, and a time of 8 hours.

[0113] The eighth stage is drying, with a drying temperature of 72°C, a humidity of 10RH, and a time of 12 hours.

[0114] The difference between the positive electrode lead paste in the positive electrode plate of this embodiment and the positive electrode lead paste in the prior art is shown in Table 1.

[0115] Positive lead paste ω(PbO)% <![CDATA[ω(Pb3O4)%]]> ω(3BS)% ω(4BS)% Prior art 31.6 28.3 34.6 5.5 Example 1 23.5 25.9 21.2 29.4

[0116] In the positive electrode plate prepared in this embodiment, the SEM image of the positive electrode lead paste is as follows: Figure 2 As shown, relative to Figure 1 For the existing positive electrode lead paste, the existing positive electrode lead paste is mostly small cylindrical crystals (tribasic lead sulfate) and a small number of large prismatic crystals (tetrabasic lead sulfate), and the two are relatively dispersed; the positive electrode lead paste prepared in this embodiment contains more cylindrical crystals (tribasic lead sulfate) and large prismatic crystals (tetrabasic lead sulfate), and the two are tightly adhered together, and the combination effect is very good.

[0117] Example 2

[0118] The difference between this embodiment and embodiment 1 is that the positive electrode grid used in this embodiment is the positive electrode grid prepared in preparation example 2.

[0119] Example 3

[0120] The difference between this embodiment and embodiment 1 is that the positive electrode grid used in this embodiment is the positive electrode grid prepared in preparation example 3.

[0121] Example 4

[0122] The difference between this embodiment and embodiment 1 is that the positive electrode grid used in this embodiment is the positive electrode grid prepared in preparation example 4.

[0123] Example 5

[0124] The difference between this embodiment and embodiment 1 is that the positive electrode grid used in this embodiment is the positive electrode grid prepared in preparation example 5.

[0125] Example 6

[0126] The difference between this embodiment and embodiment 1 is that the positive electrode grid used in this embodiment is the positive electrode grid prepared in preparation example 6.

[0127] Application Examples 1 to 6 The positive plates in the above-mentioned embodiments 1 to 6 are assembled into tubular batteries and tested. The testing method is as follows:

[0128] 1) Six batteries prepared in each example were randomly selected and connected in series, and discharged at a constant current of 0.2C10A for 2.0 h, and then charged at a constant voltage of 2.35V / cell with a current limit of 0.15C10A for 5 h as a small cycle;

[0129] 2) Repeat step 1) for a total of 30 small cycles;

[0130] 3) The 30th small cycle timed full charge: constant voltage 2.35V / cell, current limit value 0.15C10A, continuous charging time is 12 hours;

[0131] 4) Repeat steps 1) to 3) for a total of 2 large cycles (i.e. 60 small cycles);

[0132] 5) 10hr capacity test: 0.1C10A constant current discharge to 1.8V / cell, constant voltage 2.35V / cell, current limit 0.15C10A charge for 16h (after 10hr capacity test, measure the voltage, AC internal resistance and weight of each single battery);

[0133] 6) Repeat steps 1) to 5) until the battery capacity is less than 80% C10.

[0134] The test results are shown in Table 2, where Figure 3 This is a detection diagram of battery application example 1 corresponding to embodiment 1.

[0135] Table 2

[0136]

[0137]

[0138] It can be seen from Application Examples 1 to 6 and Table 2 that the C10 peak capacity of Application Example 1 reaches 140%, and the capacity performance is improved by about 15% compared with the existing technology. The peak capacity of Application Examples 2 to 6 reaches 140%, which is also improved by more than 15% compared with the existing technology. In particular, the C10 peak capacity of Application Examples 2 to 4 reaches more than 146%, which is improved by more than 20% compared with the existing technology.

[0139] It can be seen from Application Examples 1 to 6 and Table 2 that the 40% DOD charge and discharge cycle number of Application Example 1 reaches 5040 times, which is a significant improvement over the 3900 times of the prior art, and the cycle performance is improved by more than 29%. The 40% DOD charge and discharge cycle number of Application Examples 2 to 6 reaches more than 5025 times, which is also an improvement of more than 29% over the prior art. Among them, the 40% DOD charge and discharge cycle number of Application Examples 2 to 4 reaches more than 5073 times, which is an improvement of more than 30% over the prior art.

[0140] Therefore, it can be seen that the battery obtained by assembling the positive electrode grid prepared by the technical solution of the present application and the positive electrode plate prepared by the positive electrode lead paste prepared by the present application has a significantly improved capacity and cycle life compared with the prior art.

[0141] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A positive electrode grid, characterized in that: Prepared by including the following components: Ca: 0.070wt%~0.150wt%; Sn: 0.450wt%~1.250wt%; Al: 0.005wt%~0.035wt%; Ag: 0.002wt%~0.005wt%; La: 0.01wt%~0.025wt%; Pb: margin.

2. The positive electrode grid according to claim 1, characterized in that: Prepared by including the following components: Ca: 0.070wt%~0.150wt%; Sn: 0.600wt%~0.900wt%; Al: 0.015wt%~0.030wt%; Ag: 0.003wt%~0.005wt%; La: 0.012wt%~0.018wt%; Pb: margin.

3. A method for preparing a positive electrode grid according to claim 1 or 2, characterized in that: The following steps are involved: S1. Melting Lead First add some lead and heat it to make it melt; S2, slag removal Heat up, add sodium nitrate and sodium hydroxide and stir for 10-15 minutes, the lead slag will be yellow particles, remove the slag; add lead slag reducer, stir for 5-10 minutes, then stop the machine and remove the slag; S3. Adding metal components Raise the temperature again, slowly add the formulated amount of aluminum, magnesium, lanthanum, calcium, and tin while stirring, and stir for 5 to 15 minutes; S4. Cooling Add the remaining lead in the formula, cool down, and stir for 5 to 15 minutes; S5. Sampling and testing After the sampling and testing are qualified, the liquid is released; S6. Casting preparing the grid by casting; S7, Hardening Hardening in a drying room.

4. The preparation method according to claim 3, characterized in that: In the step S2, during slagging, the temperature is raised to 640±10°C; and / or, S3, adding metal components, raising the temperature to 690±10°C; And / or, S4, cooling down to 550±10°C.

5. The preparation method according to claim 3, characterized in that: In the above S6, during the casting, the casting temperature is 400°C to 480°C, and the casting plate pressure is 9 to 12 MPa.

6. The preparation method according to claim 3, characterized in that: In the S7, hardening, the temperature is 85° C. to 95° C., and the time is 4 h to 5 h.

7. A positive electrode plate, characterized in that: The invention comprises the positive electrode grid and the positive electrode lead paste as claimed in claim 1, wherein the positive electrode lead paste comprises the following components: Red lead: 15wt%~35wt%; Sulfuric acid solution: 6wt%~8wt%; Deionized water: 12wt%~18wt%; Tetrabasic lead sulfate: 0.3wt% to 0.5wt%; Graphite: 0.5wt%~1.0wt%; Polytetrafluoroethylene emulsion: 0.12wt%~0.18wt%; Antimony trioxide: 0.6wt%~1.0wt%; Stannous sulfate: 0.6wt%~1.0wt%; The rest is lead powder.

8. A method for preparing a positive electrode plate according to claim 7, characterized in that: The following steps are involved: Step 1: Add lead powder into a paste mixer, then add red lead-antimony trioxide-stannous sulfate-graphite-tetrabasic lead sulfate in sequence, and mix and stir for 4-5 minutes; Step 2: Add deionized water while stirring for 2 to 3 minutes, and continue to mix and stir for 5 to 6 minutes after adding the deionized water; during the mixing and stirring process, mix the polytetrafluoroethylene emulsion and deionized water in a volume ratio of 1:1 and add the mixed solution for 4 to 5 minutes; Step 3: After the water mixing is completed, sulfuric acid solution is added in a stirring state, and the acid addition time is controlled within 8 to 12 minutes. The maximum temperature during the acid addition process does not exceed 65°C. After the acid is added, continue mixing and stirring for 10 to 12 minutes; Step 4: Stop the machine to measure the density of the lead paste. The density of the lead paste should be between 3.4 and 3.5 g / cm 3 between; Step 5: Apply the prepared lead paste on the positive electrode grid to obtain a positive electrode plate; Step 6: The positive plate is sent to the curing and drying room for curing and drying within 40 minutes.

9. The preparation method according to claim 8, characterized in that: The curing and drying described in step 6 includes the following stages: The first stage is curing, with a curing temperature of 55°C, a humidity of 99RH, and a time of 12h; The second stage is curing, with a curing temperature of 60°C, a humidity of 95RH, and a time of 12h; The third stage is curing, with a curing temperature of 65°C, a humidity of 90RH, and a time of 6 hours; The fourth stage is curing, with a curing temperature of 65°C, a humidity of 85RH, and a time of 6 hours; The fifth stage is curing, with a curing temperature of 60°C, a humidity of 70RH, and a time of 6 hours; The sixth stage is curing, with a curing temperature of 60°C, a humidity of 55RH, and a time of 6 hours; The seventh stage is drying, with a drying temperature of 65°C, a humidity of 45RH, and a time of 8h; The eighth stage is drying, with a drying temperature of 72°C, a humidity of 10RH, and a time of 12 to 16 hours.

10. A lead-acid battery, characterized in that: The invention comprises the positive electrode plate as claimed in claim 7.